2012
DOI: 10.2341/11-212-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Activation on Resin-modified Glass Ionomer Shear Bond Strength

Abstract: SUMMARY Objective Recent studies confirmed that resin-modified glass ionomers (RMGIs) set on the basis of two competing mechanisms, an acid-base reaction and a light-activated resin polymerization. This study evaluated the effect of the setting mechanism on bond strength by measuring the shear bond strength of three RMGIs to dentin with and without light activation. Methods Sixty human molars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Lowson et al prepared a kind of resin modified glass ionomer cements (RMGICs), which were composed of polyelectrolyte solution, hydroxyethyl acrylate (HEMA)/water mixture, and a small amount of photoinitiator for polymerization of HEMA [12]. When this RMGIC is exposed to ultraviolet radiation, it quickly hardens.…”
Section: Stimuli-responsive Materialsmentioning
confidence: 99%
“…Lowson et al prepared a kind of resin modified glass ionomer cements (RMGICs), which were composed of polyelectrolyte solution, hydroxyethyl acrylate (HEMA)/water mixture, and a small amount of photoinitiator for polymerization of HEMA [12]. When this RMGIC is exposed to ultraviolet radiation, it quickly hardens.…”
Section: Stimuli-responsive Materialsmentioning
confidence: 99%
“…As this is a hybrid material, the setting reaction of RMGI sealant is initiated by light activation of the resin component, followed by the acid-base reaction of the ionomer component 1 . Although it has been suggested that the latter reaction can compensate the light attenuation that occurs in deeper areas to increase the depth of cure of RMGI 9 , the main mechanism responsible for the curing process of this type of material is light activation 8,10 . Therefore, their physical and mechanical properties can be greatly affected by factors related to the curing process 11,12 .…”
Section: Introductionmentioning
confidence: 99%